A high-hardness three-layer hollow one-component acrylic resin emulsion and preparation method thereof

The hard core resin, alkali resin and hard shell resin are organically combined by chemical methods to form a three-layer hollow single-component acrylic resin emulsion, which solves the problems of low hardness, insufficient adhesion and poor hiding after the aqueous acrylic resin emulsion formed, and achieves coating performance with high hardness, strong hiding and good adhesion.

CN115785351BActive Publication Date: 2025-04-25ZHENGZHOU ZHONGKE EMERGING IND TECH RES INST +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211700725.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-28
Publication Date
2025-04-25
Estimated Expiration
2042-12-28

AI Technical Summary

Technical Problem

The aqueous acrylic resin emulsion has low hardness, insufficient adhesion, and poor hiding power after film formation.

Method used

Chemical methods are used to organically combine hard core resin, alkali resin and hard shell resin, and the vinyl (meth)acrylic monomer is ordered to copolymerize the three-layer hollow single-component acrylic resin emulsion. During the preparation of the emulsion, the preswelling method and the polymerization method of batch feeding are used to ensure stable polymerization between ethylene monomers and the compatibility of resin.

Benefits of technology

The prepared acrylic resin emulsion has high solid content, low viscosity, uniform particle size distribution, significantly improves the hardness and adhesion of the coating film, and greatly improves the hiding power. It is suitable for the higher-end architectural coating field.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115785351B_ABST
    Figure CN115785351B_ABST
Patent Text Reader

Abstract

The present invention proposes a three-layer hollow one-component acrylic resin emulsion with high hardness and a preparation method, the technical field of water-based coatings, and is used to solve the technical problems of low hardness, insufficient adhesion, and poor hiding power of water-based acrylic resin emulsion after film formation. The present invention includes the following raw materials by weight: 20-28.5 parts of soft monomers, 72-91.6 parts of hard monomers, 5-6 parts of acrylic epoxy monomers, 26-29.5 parts of acrylic carboxyl monomers, 1-1.6 parts of initiators, 0.08-0.2 parts of catalysts, 1.2-1.8 parts of emulsifiers, 0.4-0.8 parts of pH buffers, 120-153 parts of deionized water, and 4.5-6.4 parts of neutralizers. The acrylic resin emulsion prepared by the present invention has a clear appearance, high solid content and low viscosity, good water resistance, high hardness of the single-component coating film, better gloss, and a coating prepared therefrom with strong hiding power, and can be applied to the higher-end architectural coating industry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water-based coatings, and in particular relates to a high-hardness three-layer hollow single-component acrylic resin emulsion and a preparation method thereof. Background Art

[0002] Green, environmental protection and sustainable development are the themes of development in the 21st century. Traditional solvent-based coatings produce a large amount of toxic gases and wastewater during the production and use process, which seriously pollutes the natural environment and harms human health. In recent decades, Western developed countries such as Europe and the United States have successively promulgated relevant strict laws and regulations to restrict the emission of volatile organic compounds (VOCs). In recent years, the Chinese government has also successively promulgated a series of environmental protection laws to restrict the emission of volatile organic compounds (VOCs) to promote green and low-carbon development. Therefore, the production and use of different types of traditional solvent-based coatings are restricted, and the development and use of green and environmentally friendly coatings has become a development trend now and in the future. Water-based coatings are increasingly favored by people due to their good comprehensive performance. Among them, water-based acrylic resin coatings are an important component of water-based coatings.

[0003] Since the main absorption peak of acrylic resin to light is not within the range of the solar spectrum, it has excellent light resistance and weather resistance, and can be used in the field of outdoor architectural coatings. For example, patent publication number CN108129600A discloses a hard-core soft-shell acrylic emulsion. By adjusting the ratio of soft and hard monomers added during emulsion polymerization, the water-based damping coating prepared by it has a wide damping temperature range, and can well solve the contradiction between the high-temperature damping performance of the coating and the impact resistance and flexibility, but the paint film with this as the film-forming material has insufficient hiding power; patent publication number CN109651560A discloses a high-hardness acrylic emulsion with excellent alkali resistance and a preparation method thereof, and the density and hardness of the emulsion film are improved by introducing cross-linking monomers diacetone acrylamide and adipic acid dihydrazide, but the film-forming time is still long, and high solid content and low viscosity are still difficult to take into account. It is difficult to meet the mid-to-high-end architectural coating industry. Therefore, it is very promising to develop a high-hardness acrylic resin emulsion with high hiding power that can be used in the field of architectural coatings. Summary of the invention

[0004] Aiming at the technical problems that the water-based acrylic resin emulsion has low hardness, insufficient adhesion and poor hiding power after film formation, the present invention proposes a high-hardness three-layer hollow one-component acrylic resin emulsion and a preparation method. The resin emulsion has good appearance, high solid content and low viscosity, and the hardness of the single-component coating film is high, reaching 2H, and the glossiness is good. The coating prepared with the emulsion has strong hiding power and can be applied to the higher-end architectural coating industry.

[0005] In order to achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] A high-hardness three-layer hollow single-component acrylic resin emulsion, composed of the following components in parts by weight: 20-28.5 parts of soft monomer, 72-91.6 parts of hard monomer, 5-6 parts of acrylic epoxy monomer, 26-29.5 parts of acrylic carboxyl monomer, 1-1.6 parts of initiator, 0.08-0.2 parts of catalyst, 1.2-1.8 parts of emulsifier, 0.4-0.8 parts of pH buffer, 120-153 parts of deionized water, and 4.5-6.4 parts of neutralizer;

[0007] The mass ratio of the soft monomer to the hard monomer in the core resin is 1:(1.8-2.3), wherein the hard monomer is methyl methacrylate; the mass ratio of the acrylic epoxy monomer in the core resin to the acrylic carboxyl monomer in the base resin is 1:(4.6-5);

[0008] The emulsifier is any one or a combination of two or more of sodium vinyl sulfonate, monopolyethylene glycol acrylate, and terminal acrylate-based waterborne polyurethane;

[0009] The particle size of the latex particles in the prepared acrylic emulsion is 170-200nm.

[0010] The preparation method of the resin emulsion comprises the following steps:

[0011] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 75-85° C. in a water bath, and continuously stirred mechanically at a speed of 150-200 r / min;

[0012] (2) 0.38-0.48 times of soft monomer, 0.24-0.36 times of hard monomer and acrylic epoxy monomer are added to a 150 mL flask, and mixed evenly to obtain a core resin pre-emulsion A; catalyst, 0.28-0.35 times of soft monomer, 0.32-0.48 times of hard monomer and 0.93-0.97 times of acrylic carboxyl monomer are added to a 150 mL flask, and mixed evenly to obtain a base resin pre-emulsion B; 0.22-0.28 times of soft monomer, 0.22-0.40 times of hard monomer, 0.03-0.07 times of acrylic carboxyl monomer and 0.25 times of initiator are added to a 150 mL flask, and mixed evenly to obtain a shell resin pre-emulsion C;

[0013] (3) 1 / 7-1 / 5 of the mixed solution of pre-emulsion A is uniformly added to a 500 mL four-necked flask, and after uniform stirring for 3-8 minutes, 1 / 40-3 / 40 of the initiator is added, and after keeping the temperature for 15-25 minutes, 1 / 5-2 / 5 of the initiator is added, and then the remaining mixed solution of pre-emulsion A is uniformly added dropwise for 45-50 minutes, and then the temperature is kept for 20-40 minutes;

[0014] (4) After the insulation is completed, 1 / 7-1 / 5 of the mixed solution of pre-emulsion B is added, and after stirring at a uniform speed for 3-8 minutes, 3 / 40-5 / 40 of the initiator is added. After the insulation reaction is carried out for 20-30 minutes, 1 / 5-2 / 5 of the initiator is added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate, and the addition time is maintained at 100-120 minutes. After the addition is completed, the insulation reaction is carried out for 20-40 minutes;

[0015] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 65-75 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0016] (6) When the temperature reaches 40° C., add a neutralizing agent and stir evenly, and adjust the pH to 8.5-9 to obtain a high-hardness three-layer hollow one-component acrylic resin emulsion.

[0017] Preferably, the step (3) is as follows: 1 / 6 of the mixed solution of pre-emulsion A is uniformly added to a 500 mL four-necked flask, 1 / 20 of the initiator is added after uniform stirring for 5 minutes, 3 / 10 of the initiator is added after heat preservation for 20 minutes, and then the remaining mixed solution of pre-emulsion A is dripped at a uniform speed, the dripping is completed for 45-50 minutes, and the heat preservation is continued for 30 minutes.

[0018] Preferably, in step (4), after the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after uniform stirring for 5 minutes, 2 / 20 of the initiator is added, and after the insulation reaction is carried out for 25 minutes, 3 / 10 of the initiator is added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate, and the dropping time is maintained at 100-120 minutes. After the addition is completed, the insulation reaction is carried out for 30 minutes.

[0019] The hard monomers of the base resin and the shell resin are a combination of methyl methacrylate and styrene, and the mass ratios of methyl methacrylate to styrene are (2-2.2):1 and (3-3.2):1 respectively.

[0020] The soft monomer is lauryl methacrylate; the acrylic epoxy monomer is any one of glycidyl methacrylate or glycidyl acrylate; and the acrylic carboxyl monomer is any one of methacrylic acid or acrylic acid.

[0021] The catalyst is tetrabutylammonium bromide; the initiator is any one of ammonium persulfate or potassium persulfate.

[0022] The pH buffer is one or a combination of sodium bicarbonate or ammonium bicarbonate; the neutralizer is one or a combination of triethylamine and NN dimethylethanolamine.

[0023] The high-hardness three-layer hollow one-component acrylic resin emulsion has high solid and low viscosity, uniform particle size distribution, and the glossiness of the varnish after film formation is more than 100%. The hardness and adhesion are 2H and 0 respectively, and it shows excellent hiding power and can be used in higher-end construction fields.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention uses a chemical method to organically combine a hard core resin, a base resin and a hard shell resin, utilizes particle design to orderly copolymerize vinyl (meth) acrylic monomers, and finally dissolves the base resin through neutralization with amine to form a hollow structure, thereby synthesizing a three-layer hollow single-component acrylic resin emulsion. In the preparation process, a pre-swelling method and an intermittent feeding polymerization method are adopted, which, firstly, ensure the stability of polymerization between vinyl monomers and control the composition of the copolymer; secondly, mutual penetration grafting occurs between the core, base and shell resins, greatly improving the compatibility of the core, base and shell resins, effectively solving the stability of the acrylic emulsion and increasing other comprehensive properties.

[0026] (2) The present invention chemically embeds the emulsifier into the acrylic resin molecular chain through the design of the molecular structure, thereby avoiding the risk of demulsification to a large extent and improving the stability of the acrylic resin emulsion in storage and use; in addition, by regulating and limiting the mass ratio of the vinyl (meth) acrylic soft and hard monomers of the shell and core resins, the soft and hard monomers are guaranteed to be copolymerized on the polymer chain in an orderly manner, and the hardness of the polymerization is improved; at the same time, the formation of the three-layer hollow resin structure causes the incident light source to undergo multiple refractions and scatterings, giving the coating film excellent hiding power.

[0027] (3) The acrylic resin emulsion prepared by the present invention uses water as solvent, does not produce harmful substances, is green and environmentally friendly, and has a simple process and broad market application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 This is a particle structure diagram of acrylic resin emulsion;

[0030] Figure 2 It is a performance comparison chart of Example 1 and Comparative Examples 1-4. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. The unit of mass parts in the following embodiments is gram.

[0032] Example 1

[0033] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0034] Soft monomer: lauryl methacrylate, 20.5 parts;

[0035] Hard monomers: methyl methacrylate and styrene, accounting for 58 parts and 16 parts respectively;

[0036] Acrylic epoxy monomer: glycidyl methacrylate, 5 parts;

[0037] Acrylic acid carboxyl monomer: methacrylic acid, 26 parts;

[0038] Initiator: ammonium persulfate, 1 part;

[0039] Catalyst: tetrabutylammonium bromide, 0.08 parts;

[0040] pH buffer: sodium bicarbonate, 0.4 parts;

[0041] Emulsifier: sodium vinyl sulfonate, 1.2 parts;

[0042] Deionized water: 120 parts;

[0043] Neutralizing agent: triethylamine, 4.5 parts.

[0044] The preparation process is:

[0045] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 75 °C in a water bath, and continuously stirred at a speed of 150 r / min;

[0046] (2) 9.5 parts of lauryl methacrylate, 20 parts of methyl methacrylate and 5 parts of glycidyl methacrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 6 parts of lauryl methacrylate, 20 parts of methyl methacrylate, 10 parts of styrene and 25 parts of methacrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 5 parts of lauryl methacrylate, 18 parts of methyl methacrylate, 6 parts of styrene, 1 part of methacrylic acid and 0.25 parts of ammonium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0047] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.05 parts of ammonium persulfate was added. After keeping the temperature for 25 minutes, 0.3 parts of ammonium persulfate was added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise for 45 minutes, and then kept for 30 minutes;

[0048] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after uniform stirring for 5 minutes, 0.1 parts of ammonium persulfate is added. After the insulation reaction for 25 minutes, 0.3 parts of ammonium persulfate is added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate. The addition time is maintained at 100 minutes. After the addition is completed, the insulation reaction is continued for 30 minutes;

[0049] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 75 min, and keep the temperature for reaction for 2 h after the addition is completed;

[0050] (6) When the temperature reaches 40°C, triethylamine is added and stirred evenly, and the pH is adjusted to 9 to obtain a high-hardness three-layer hollow one-component acrylic resin emulsion, the structure of which is as follows: Figure 1 shown.

[0051] Example 2

[0052] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0053] Soft monomer: lauryl methacrylate, 28.5 parts;

[0054] Hard monomers: methyl methacrylate and styrene, accounting for 72 parts and 18.8 parts respectively;

[0055] Acrylic epoxy monomer: glycidyl methacrylate, 6 parts;

[0056] Acrylic acid carboxyl monomer: methacrylic acid, 29.5 parts;

[0057] Initiator: potassium persulfate, 1.6 parts;

[0058] Catalyst: tetrabutylammonium bromide, 0.2 parts;

[0059] pH buffer: ammonium bicarbonate, 0.8 parts;

[0060] Emulsifier: acrylate-terminated waterborne polyurethane, 1.8 parts;

[0061] Deionized water: 153 parts;

[0062] Neutralizing agent: NN dimethylethanolamine, 6.4 parts.

[0063] The preparation process is:

[0064] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 85 °C in a water bath, and continuously stirred mechanically at a speed of 200 r / min;

[0065] (2) 11 parts of lauryl methacrylate, 25.3 parts of methyl methacrylate, and 6 parts of glycidyl methacrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; 9.5 parts of lauryl methacrylate, 24 parts of methyl methacrylate, 11.3 parts of styrene, and 28 parts of methacrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 8 parts of lauryl methacrylate, 23.5 parts of methyl methacrylate, 7.5 parts of styrene, 1.5 parts of methacrylic acid, and 0.4 parts of potassium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0066] 27.6 parts of methyl methacrylate, 10 parts of lauryl methacrylate and 6 parts of glycidyl methacrylate were put into a 150 mL flask and mixed evenly to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 8.5 parts of lauryl methacrylate, 22.7 parts of methyl methacrylate, 11.3 parts of styrene and 28 parts of methacrylic acid were put into a 150 mL flask and mixed evenly to obtain a base resin pre-emulsion B; 8 parts of lauryl methacrylate, 21.7 parts of methyl methacrylate, 7.5 parts of styrene, 1.5 parts of methacrylic acid and 0.4 parts of potassium persulfate were put into a 150 mL flask and mixed evenly to obtain a shell resin pre-emulsion C;

[0067] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.08 parts of potassium persulfate was added. After keeping the temperature for 25 minutes, 0.48 parts of potassium persulfate was added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise. The addition was completed after 50 minutes, and the temperature was kept for another 30 minutes;

[0068] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after stirring at a uniform speed for 5 minutes, 0.16 parts of potassium persulfate are added. After the insulation reaction for 25 minutes, 0.48 parts of potassium persulfate are added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate. The dropping time is maintained at 120 minutes. After the addition is completed, the insulation reaction is continued for 30 minutes;

[0069] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 75 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0070] (6) When the temperature reaches 40° C., NN dimethylethanolamine is added and stirred evenly, and the pH is adjusted to 8.5 to obtain a three-layer hollow one-component acrylic resin emulsion with high hardness.

[0071] Example 3

[0072] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0073] Soft monomer: lauryl methacrylate, 25 parts;

[0074] Hard monomers: methyl methacrylate and styrene, accounting for 64 parts and 17.5 parts respectively;

[0075] Acrylic epoxy monomer: glycidyl acrylate, 5.5 parts;

[0076] Acrylic acid carboxyl monomer: acrylic acid, 28.3 parts;

[0077] Initiator: potassium persulfate, 1.2 parts;

[0078] Catalyst: tetrabutylammonium bromide, 0.15 parts;

[0079] pH buffer: ammonium bicarbonate, 0.7 parts;

[0080] Emulsifier: acrylate-terminated waterborne polyurethane, 1.5 parts;

[0081] Deionized water: 138 parts;

[0082] Neutralizing agent: triethylamine, NN dimethylethanolamine, accounting for 3 parts and 2.4 parts respectively.

[0083] The preparation process is:

[0084] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 83 °C in a water bath, and continuously stirred at a speed of 180 r / min;

[0085] (2) 11 parts of lauryl methacrylate, 21 parts of methyl methacrylate and 5.5 parts of glycidyl acrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 8 parts of lauryl methacrylate, 22 parts of methyl methacrylate, 10.5 parts of styrene and 27 parts of acrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 6 parts of lauryl methacrylate, 21 parts of methyl methacrylate, 7 parts of styrene, 1.3 parts of acrylic acid and 0.3 parts of potassium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0086] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.06 parts of potassium persulfate were added. After keeping the temperature for 25 minutes, 0.36 parts of potassium persulfate were added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise. The addition was completed over 47 minutes, and the mixture was kept for 30 minutes;

[0087] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after stirring at a uniform speed for 5 minutes, 0.12 parts of potassium persulfate are added. After the insulation reaction for 25 minutes, 0.36 parts of potassium persulfate are added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate. The dropping time is maintained at 110 minutes. After the addition is completed, the temperature is kept for 30 minutes;

[0088] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 70 min, and keep the temperature for reaction for 2.5 h after the addition is completed;

[0089] (6) When the temperature reaches 40° C., triethylamine and NN dimethylethanolamine are added and stirred evenly, and the pH is adjusted to 8.9 to obtain a three-layer hollow acrylic resin emulsion with high hiding power that can be used in the construction field.

[0090] Example 4

[0091] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0092] Soft monomer: lauryl methacrylate, 24 parts;

[0093] Hard monomers: methyl methacrylate and styrene, accounting for 67 parts and 18 parts respectively;

[0094] Acrylic epoxy monomer: glycidyl acrylate, 5.6 parts;

[0095] Acrylic acid carboxyl monomer: methacrylic acid, 27.2 parts;

[0096] Initiator: ammonium persulfate, 1.4 parts;

[0097] Catalyst: tetrabutylammonium bromide, 0.15 parts;

[0098] pH buffer: sodium bicarbonate, ammonium bicarbonate, 0.2 parts and 0.3 parts respectively;

[0099] Emulsifier: acrylate monopolyethylene glycol ester, 1.4 parts;

[0100] Deionized water: 140 parts;

[0101] Neutralizer: NN dimethylethanolamine, 5.5 parts.

[0102] The preparation process is:

[0103] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 83 °C in a water bath, and continuously stirred at 200 r / min;

[0104] (2) 11 parts of lauryl methacrylate, 24 parts of methyl methacrylate and 5.6 parts of glycidyl acrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 7.5 parts of lauryl methacrylate, 22.6 parts of methyl methacrylate, 11.2 parts of styrene and 26 parts of methacrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 5.5 parts of lauryl methacrylate, 20.4 parts of methyl methacrylate, 6.8 parts of styrene, 1.2 parts of methacrylic acid and 0.35 parts of ammonium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0105] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.07 parts of ammonium persulfate was added. After keeping the temperature for 25 minutes, 0.42 parts of ammonium persulfate was added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise for 49 minutes, and then kept for 30 minutes;

[0106] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after uniform stirring for 5 minutes, 0.14 parts of ammonium persulfate are added. After the insulation reaction is carried out for 25 minutes, 0.42 parts of ammonium persulfate are added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate. The addition time is maintained at 100 minutes. After the addition is completed, the insulation reaction is carried out for 30 minutes;

[0107] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 65 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0108] (6) When the temperature reaches 40° C., NN dimethylethanolamine is added and stirred evenly, and the pH is adjusted to 8.5 to obtain a three-layer hollow one-component acrylic resin emulsion with high hardness.

[0109] Example 5

[0110] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0111] Soft monomer: lauryl methacrylate, 24 parts;

[0112] Hard monomers: methyl methacrylate and styrene, accounting for 65 parts and 18.5 parts respectively;

[0113] Acrylic epoxy monomer: glycidyl methacrylate, 5.8 parts;

[0114] Acrylic acid carboxyl monomer: methacrylic acid, 29 parts;

[0115] Initiator: potassium persulfate, 1.5 parts;

[0116] Catalyst: tetrabutylammonium bromide, 0.2 parts;

[0117] pH buffer: ammonium bicarbonate, 0.6 parts;

[0118] Emulsifier: sodium vinyl sulfonate, acrylate-terminated waterborne polyurethane, 0.6 parts and 0.6 parts respectively;

[0119] Deionized water: 138 parts;

[0120] Neutralizing agent: triethylamine, 5.4 parts.

[0121] The preparation process is:

[0122] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 78 °C in a water bath, and continuously stirred mechanically at a speed of 200 r / min;

[0123] (2) 10.5 parts of lauryl methacrylate, 20.5 parts of methyl methacrylate and 5.8 parts of glycidyl methacrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 7 parts of lauryl methacrylate, 23.2 parts of methyl methacrylate, 11.5 parts of styrene and 27.2 parts of methacrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 6.5 parts of lauryl methacrylate, 21.3 parts of methyl methacrylate, 7 parts of styrene, 1.8 parts of methacrylic acid and 0.375 parts of potassium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0124] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.075 parts of potassium persulfate were added. After keeping the temperature for 25 minutes, 0.45 parts of potassium persulfate were added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise. The addition was completed after 50 minutes, and the temperature was kept for another 30 minutes;

[0125] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after stirring at a uniform speed for 5 minutes, 0.15 parts of potassium persulfate are added. After the insulation reaction is continued for 25 minutes, 0.45 parts of potassium persulfate are added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate. The addition time is maintained at 120 minutes. After the addition is completed, the insulation reaction is continued for 30 minutes;

[0126] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 75 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0127] (6) When the temperature reaches 40° C., triethylamine is added and stirred evenly, and the pH is adjusted to 9 to obtain a three-layer hollow one-component acrylic resin emulsion with high hardness.

[0128] Comparative Example 1

[0129] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0130] Soft monomer: lauryl methacrylate, 20.5 parts;

[0131] Hard monomers: methyl methacrylate and styrene, accounting for 58 parts and 16 parts respectively;

[0132] Acrylic epoxy monomer: glycidyl methacrylate, 5 parts;

[0133] Acrylic acid carboxyl monomer: methacrylic acid, 26 parts;

[0134] Initiator: ammonium persulfate, 1 part;

[0135] Catalyst: tetrabutylammonium bromide, 0.08 parts;

[0136] pH buffer: sodium bicarbonate, 0.4 parts;

[0137] Emulsifier: 1.2 parts of sodium lauryl sulfate;

[0138] Deionized water: 120 parts;

[0139] Neutralizing agent: triethylamine, 4.5 parts.

[0140] The preparation process is:

[0141] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 75 °C in a water bath, and continuously stirred at a speed of 150 r / min;

[0142] (2) 9.5 parts of lauryl methacrylate, 20 parts of methyl methacrylate and 5 parts of glycidyl methacrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 6 parts of lauryl methacrylate, 20 parts of methyl methacrylate, 10 parts of styrene and 25 parts of methacrylic acid were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 5 parts of lauryl methacrylate, 18 parts of methyl methacrylate, 6 parts of styrene, 1 part of methacrylic acid and 0.25 parts of ammonium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0143] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.05 parts of ammonium persulfate was added. After keeping the temperature for 25 minutes, 0.3 parts of ammonium persulfate was added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise for 45-50 minutes, and then kept for 30 minutes;

[0144] (4) After the insulation is completed, 1 / 6 of the mixed solution of pre-emulsion B is added, and after uniform stirring for 5 minutes, 0.1 parts of ammonium persulfate is added. After the insulation reaction for 25 minutes, 0.3 parts of ammonium persulfate is added, and then the remaining mixed solution of pre-emulsion B is added dropwise at a very slow rate, and the addition time is maintained at 100-120 minutes. After the addition is completed, the insulation reaction is continued for 30 minutes;

[0145] (5) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 65-75 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0146] (6) When the temperature reaches 40° C., triethylamine is added and stirred evenly, and the pH is adjusted to 8.5-9 to obtain a three-layer hollow one-component acrylic resin emulsion with high hardness.

[0147] Comparative Example 2

[0148] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0149] Soft monomer: lauryl methacrylate, 20.5 parts;

[0150] Hard monomers: methyl methacrylate and styrene, accounting for 58 parts and 16 parts respectively;

[0151] Acrylic epoxy monomer: glycidyl methacrylate, 5 parts;

[0152] Acrylic acid carboxyl monomer: methacrylic acid, 26 parts;

[0153] Initiator: ammonium persulfate, 1 part;

[0154] Catalyst: tetrabutylammonium bromide, 0.08 parts;

[0155] pH buffer: sodium bicarbonate, 0.4 parts;

[0156] Emulsifier: 1.2 parts of sodium lauryl sulfate;

[0157] Deionized water: 120 parts;

[0158] Neutralizing agent: triethylamine, 4.5 parts.

[0159] The preparation process is:

[0160] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 75 °C in a water bath, and continuously stirred at a speed of 150 r / min;

[0161] (2) 9.5 parts of lauryl methacrylate, 20 parts of methyl methacrylate, 5 parts of glycidyl methacrylate and 0.35 parts of emulsifier were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 6 parts of lauryl methacrylate, 20 parts of methyl methacrylate, 10 parts of styrene, 25 parts of methacrylic acid and 0.4 parts of emulsifier were added to a 150 mL flask and mixed to obtain a base resin pre-emulsion B; 5 parts of lauryl methacrylate, 18 parts of methyl methacrylate, 6 parts of styrene, 1 part of methacrylic acid and 0.25 parts of emulsifier were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0162] (3) Add the mixed solution of core resin pre-emulsion A evenly to a 500 mL four-necked flask, and add it dropwise for 50-60 minutes; then add the mixed solution of pre-emulsion B dropwise for 60-70 minutes; finally, add the mixed solution of pre-emulsion C dropwise for 65-75 minutes, and keep the temperature for reaction for 1.5-2.5 hours after the addition is completed;

[0163] (4) When the temperature reaches 40° C., triethylamine is added and stirred evenly, and the pH is adjusted to 8.5-9 to obtain a three-layer hollow one-component acrylic resin emulsion.

[0164] Comparative Example 3

[0165] A high-hardness three-layer hollow one-component acrylic resin emulsion, calculated by mass parts as follows:

[0166] Soft monomer: lauryl methacrylate, 20.5 parts;

[0167] Hard monomers: methyl methacrylate and styrene, accounting for 58 parts and 16 parts respectively;

[0168] Acrylic epoxy monomer: glycidyl methacrylate, 5 parts;

[0169] Acrylic acid carboxyl monomer: methacrylic acid, 26 parts;

[0170] Initiator: ammonium persulfate, 1 part;

[0171] Catalyst: tetrabutylammonium bromide, 0.08 parts;

[0172] pH buffer: sodium bicarbonate, 0.4 parts;

[0173] Emulsifier: sodium vinyl sulfonate, 1.2 parts;

[0174] Deionized water: 120 parts;

[0175] Neutralizing agent: triethylamine, 4.5 parts.

[0176] The preparation process is:

[0177] (1) Deionized water, emulsifier and pH buffer were added to a 500 mL four-necked flask in sequence, heated to 75 °C in a water bath, and continuously stirred at a speed of 150 r / min;

[0178] (2) 40 parts of methyl methacrylate, 10 parts of styrene, 16.5 parts of lauryl methacrylate, and 5 parts of glycidyl methacrylate were added to a 150 mL flask and mixed to obtain a core resin pre-emulsion A; tetrabutylammonium bromide, 4 parts of lauryl methacrylate, 18 parts of methyl methacrylate, 6 parts of styrene, 26 parts of methacrylic acid, and 0.25 parts of ammonium persulfate were added to a 150 mL flask and mixed to obtain a shell resin pre-emulsion C;

[0179] (3) 1 / 6 of the mixed solution of the core resin pre-emulsion A was uniformly added to a 500 mL four-necked flask, and after uniform stirring for 5 minutes, 0.15 parts of ammonium persulfate was added. After keeping the temperature for 25 minutes, 0.6 parts of ammonium persulfate was added, and then the remaining mixed solution of the pre-emulsion A was uniformly added dropwise for 45-50 minutes, and then kept for 30 minutes;

[0180] (4) Finally, slowly add the mixed solution of pre-emulsion C dropwise for 65-75 min, and keep the temperature for reaction for 1.5-2.5 h after the addition is completed;

[0181] (5) When the temperature reaches 40° C., triethylamine is added and stirred evenly, and the pH is adjusted to 8.5-9 to obtain a one-component acrylic resin emulsion.

[0182] Comparative Example 4

[0183] An acrylic emulsion, the preparation method of which is compared with the acrylic emulsion prepared in Example 1 of Patent Publication No. CN109651560A, a high-hardness acrylic emulsion with excellent alkali resistance and its preparation method.

[0184] Test Case

[0185] To further illustrate the high-hardness three-layer hollow one-component acrylic resin emulsion disclosed in the present invention, the present invention also conducted corresponding tests on Examples 1 to 5, and the test method is as follows:

[0186] 1. Emulsion stability test

[0187] (1) Mechanical stability test: First, filter the emulsion with a 100-mesh screen, then vigorously stir it at 5000 rpm for 10 minutes in a power agitator, and then filter it with a 100-mesh screen. If no gel appears, the emulsion has good mechanical properties and passes the test. If gel appears, dry the filtered gel in an oven at 105°C to constant weight and weigh it. The more dry coagulants there are, the worse the mechanical stability.

[0188] (2) Freezing stability test: Place 50 mL of the emulsion sample into a cylindrical plastic container or glass container of about 100 mL, taking care not to mix in bubbles. Cover the container with a lid and seal it. Place it in a -20±2°C low-temperature oven. Take it out after 18 hours and place it in a 25±2°C constant temperature oven for 6 hours. Repeat this process five times. Open the container and stir it with a glass rod. Observe the sample for any abnormalities such as lumps or gels. Use a glass rod to spread the sample on a glass plate into a uniform thin layer and observe for the presence of flocs. If there are no flocs, the sample passes the test.

[0189] (3) Storage stability test: The prepared emulsion sample was placed in a 50°C oven and kept at a constant temperature for 2 weeks. The sample was taken out and placed at room temperature for observation. If no stratification, gelation, etc. was observed, the sample passed the test.

[0190] (4) Dilution stability test: dilute and mix the emulsion sample in the ratio of emulsion: water = 1:10, and place it for 48 hours. If no demulsification or stratification occurs, the test is passed.

[0191] 2. Coating performance test

[0192] (1) Test of coating surface drying time: The emulsion prepared in the example was evenly applied on a polytetrafluoroethylene plate, dried at a constant temperature of 25° C., and the coating surface drying time was tested according to the method of GB1728-79.

[0193] (2) Coating hardness test: The hardness of the emulsion coating prepared in the example was tested according to the method of GB / T6739-2006.

[0194] (3) Coating adhesion test: The adhesion of the emulsion coating prepared in the examples was tested according to the method of GB / T9286-1998.

[0195] (4) Film gloss test: According to GB / T9754-2007 standard, the gloss of the emulsion film in the example was tested using the 60-degree specular gloss measurement method.

[0196] (5) Water resistance test of coating film: GB / T1733-1993 standard was used to test the water resistance of the emulsion coating film in the example. If the coating film did not bubble or fall off within 96 hours and slight discoloration was allowed, it was considered to have passed the test.

[0197] Table 1 Performance Structure of the Tests of Implementations 1-5 and Comparative Examples 1, 2 and 4

[0198]

[0199]

[0200] In order to further examine the hiding power of the three-layer hollow acrylic resin emulsion of the present invention as the main film-forming material in the coating, Example 1 and Comparative Example 3 and the commercially available acrylic resin emulsion Archsol 8171 were ground by mixed vibration at high speed according to the method in Formula Table 2, and the coating films were dried and tested for hiding power. The test results are shown in Table 3.

[0201] Testing method: Take an appropriate amount of ground coating and place it on one end of a standard black and white cardboard, use an automatic coating machine to quickly coat it, place it under a certain temperature until the surface is dry, use a spectrophotometer to measure the reflectivity of the blackboard and whiteboard, and use the contrast ratio to reflect the hiding power of the coating. The calculation is as follows:

[0202] Contrast ratio = (blackboard reflectivity / whiteboard reflectivity) × 100%. The larger the contrast ratio, the better the covering power of the paint, which means the better the covering power of the acrylic resin emulsion.

[0203] Table 2 Experimental formula using mixed vibration high-speed grinding

[0204] raw material wt / % Acrylic Emulsion 63 Titanium dioxide 35 BYK-025 water-based defoamer 0.5 BYK-341 water-based substrate wetting agent 0.8 BYK-154 aqueous dispersant 1.3

[0205] Table 3 Hiding power test results

[0206] raw material Hiding power / % Example 1 91 Comparative Example 3 71 Commercially available 70

[0207] The patent of this application uses chemical methods to prepare a high-hardness three-layer hollow single-component acrylic resin emulsion by pre-swelling method and intermittent feeding polymerization of hard resin, base resin and shell resin. As shown in Table 1: the solid content of the emulsion is as high as about 51%, the viscosity is about 67KU, the particle size distribution is uniform, the surface drying time of the coating is 26min-28min, the hardness and adhesion of the coating are 2H and 0 levels respectively, and the glossiness can be as high as 105° or more. 1) Example 1 and Comparative Example 1, the emulsifier used in Comparative Example 1 is sodium dodecyl sulfate, and the others remain unchanged. From Table 1 and Figure 2 The test results show that the stability of the resin emulsion in Comparative Example 1 cannot pass the test. This is because the emulsifier is prone to demulsification in some environments, resulting in instability of the resin emulsion, and migration during the drying process of the resin coating, thereby reducing the water resistance of the coating. The emulsifier used in the present invention can react with the vinyl monomer and connect to the main chain of the molecule without demulsification. Therefore, it has good stability and water resistance. 2) Example 1 and Comparative Example 2, Comparative Example 2 adopts the ordinary dripping method, and the others remain unchanged. Figure 2 It can be seen that the resin emulsion is unstable during the polymerization process. The viscosity is low at the beginning of the polymerization, but the viscosity becomes higher in the later stage of the polymerization. The viscosity of the final tested emulsion is about 90KU. The viscosity of the resin emulsion is relatively stable by using the polymerization method of the invention patent of this application. This is because molecular grafting or mutual penetration occurs between the core-subtraction-shell during the polymerization process, ensuring the compatibility between the different polymers of the core-base-shell layer. 3) Example 1 and Comparative Example 4, Comparative Example 4 (application number CN201811652011) introduces silicone and adds cross-linking monomers diacetone acrylamide and adipic acid dihydrazide to cross-link the surface of the emulsion film to form a dense layer, but the hardness of the coating is only 1H. The invention patent of this application, without introducing a cross-linking monomer, limits the ratio of soft and hard monomers and adjusts the polymerization process to prepare a high-hardness single-component acrylic emulsion, and the coating hardness is as high as 2H. 4) The coating films prepared by Example 1, Comparative Example 3 and the commercially available emulsion according to the formula of Table 2 were tested for their hiding power, as shown in Table 3 and Figure 2 As shown. The hiding power of the coating film prepared with the emulsion of Example 1 as the main film-forming substance is as high as 91%, while the hiding power of the coating film prepared with the emulsion of Comparative Example 3 and the commercially available emulsion as the main film-forming substance is about 70%, indicating that the three-layer hollow single-component acrylic emulsion prepared by the invention patent of this application as the main film-forming substance can improve the hiding power of the coating film. This is because the formation of the three-layer hollow resin structure causes the incident light source to undergo multiple refractions and scatterings, giving the coating film excellent hiding power.

[0208] In summary, the high-hardness three-layer hollow one-component acrylic resin emulsion and preparation method proposed in the invention patent of this application can be used to solve the technical problems of low hardness, insufficient adhesion and poor hiding power of water-based acrylic resin emulsion after film formation. The prepared acrylic resin emulsion has a clear appearance, high solid content and low viscosity, uses water as a solvent, does not produce harmful substances, is green and environmentally friendly, and has a simple process, and has broad market application value.

[0209] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a high-hardness three-layer hollow one-component acrylic resin emulsion, characterized in that: The steps are as follows: (1) uniformly mixing a soft monomer, a hard monomer and an acrylic epoxy monomer to obtain a core resin pre-emulsion; uniformly mixing a catalyst, a soft monomer, a hard monomer and an acrylic carboxyl monomer to obtain a base resin pre-emulsion; uniformly mixing a soft monomer, a hard monomer, an acrylic carboxyl monomer and an initiator to obtain a shell resin pre-emulsion; uniformly mixing deionized water, an emulsifier and a pH buffer to obtain an emulsifier solution; (2) adding the core resin pre-emulsion and the initiator into the emulsifier solution by intermittent feeding; (3) adding the alkaline resin pre-emulsion and the initiator to the solution of step (2) by intermittent feeding; (4) adding the shell resin pre-emulsion to the solution of step (3) to react, and adding a neutralizing agent after the reaction is completed to obtain a three-layer hollow single-component acrylic resin emulsion with high hardness; The preparation method of each solution in step (1) is: Core resin pre-emulsion: 0.38-0.48 times of soft monomer, 0.24-0.36 times of hard monomer and acrylic epoxy monomer are uniformly mixed to obtain core resin pre-emulsion; Alkaline resin pre-emulsion: the catalyst, 0.28-0.35 times of soft monomer, 0.32-0.48 times of hard monomer and 0.93-0.97 times of acrylic acid carboxyl monomer are uniformly mixed to obtain the alkaline resin pre-emulsion; Shell resin pre-emulsion: 0.22-0.28 times of soft monomer, 0.22-0.40 times of hard monomer, 0.03-0.07 times of acrylic acid carboxyl monomer and 0.25 times of initiator are mixed evenly to obtain shell resin pre-emulsion; Emulsifier solution: Mix deionized water, emulsifier and pH buffer, heat to 75-85°C, and stir evenly to obtain an emulsifier solution; The step of intermittent feeding in step (2) is as follows: uniformly adding 1 / 7-1 / 5 of the core resin pre-emulsion to the emulsifier solution, stirring at a uniform speed for 3-8 minutes, adding 1 / 40-3 / 40 of the initiator, keeping the temperature for reaction for 15-25 minutes, adding 1 / 5-2 / 5 of the initiator, then uniformly dropping the remaining core resin pre-emulsion for 45-50 minutes, and keeping the temperature for reaction for 20-40 minutes after the dropping is completed; The step of intermittent feeding in step (3) is as follows: add 1 / 7-1 / 5 of the alkaline resin pre-emulsion to the solution of step (2), stir at a constant speed for 3-8 minutes, then add 3 / 40-5 / 40 of the initiator, keep the mixture warm for 20-30 minutes, then add 1 / 5-2 / 5 of the initiator, then dropwise add the remaining alkaline resin pre-emulsion at a constant rate for 100-120 minutes, and keep the mixture warm for 20-40 minutes after the addition is completed; The specific steps of step (4) are: adding the shell resin pre-emulsion to the solution of step (3) for 65-75 minutes, and keeping the temperature for reaction for 1.5-2.5 hours after the addition is completed; then adding a neutralizing agent at a temperature below 40°C and stirring evenly, adjusting the pH to 8.5-9, and obtaining a high-hardness three-layer hollow single-component acrylic resin emulsion; The mass parts of the components in the preparation method are: 20-28.5 parts of soft monomer, 72-91.6 parts of hard monomer, 5-6 parts of acrylic epoxy monomer, 26-29.5 parts of acrylic carboxyl monomer, 1-1.6 parts of initiator, 0.08-0.2 parts of catalyst, 1.2-1.8 parts of emulsifier, 0.4-0.8 parts of pH buffer, 120-153 parts of deionized water, and 4.5-6.4 parts of neutralizer; The mass ratio of the soft monomer to the hard monomer in the core resin pre-emulsion is 1:(1.8-2.3), wherein the hard monomer is methyl methacrylate; the mass ratio of the acrylic epoxy monomer in the core resin pre-emulsion to the acrylic carboxyl monomer in the base resin pre-emulsion is 1:(4.6-5); The hard monomers in the base resin pre-emulsion and the shell resin pre-emulsion are composed of methyl methacrylate and styrene, the mass ratio of methyl methacrylate to styrene in the base resin pre-emulsion is (2-2.2):1, and the mass ratio of methyl methacrylate to styrene in the shell resin pre-emulsion is (3-3.2):1; the emulsifier is any one of sodium vinyl sulfonate, monopolyethylene glycol acrylate, and terminal acrylate-based waterborne polyurethane, or a combination of two or more thereof; The soft monomer is lauryl methacrylate; the acrylic epoxy monomer is glycidyl methacrylate or glycidyl acrylate; the acrylic carboxyl monomer is methacrylic acid or acrylic acid; the catalyst is tetrabutylammonium bromide; the initiator is ammonium persulfate or potassium persulfate; the pH buffer is sodium bicarbonate or ammonium bicarbonate or a combination of the two; and the neutralizer is triethylamine and NN dimethylethanolamine or a combination of the two.

2. The three-layer hollow one-component acrylic resin emulsion prepared by the method of claim 1, characterized in that: The latex particles in the three-layer hollow single-component acrylic resin emulsion include a core resin layer, a base resin layer and a shell resin layer in sequence from the inside to the outside.

Citation Information

Patent Citations

  • Hard-core and soft-shell type acrylic emulsion, and preparation method and application thereof

    CN108129600A

  • High hardness acrylic emulsion with excellent alkali resistant property and preparation method thereof

    CN109651560A